Determinants of Corporate Actual Cash Taxes Paid: A New Insight from Nigeria - Asien, Etumudon Ndidi (The Journal of Accounting and Management, 2022)
This study examines the hypotheses that revenues, profitability, intangible assets, and percentage of foreign shareholdings, external auditors, tax haven status and firm size do not associate with corporate actual cash taxes paid. The main results of pooled OLS multivariate regression suggest that revenue, intangible assets, and percentage of foreign shareholdings are directly and significantly associated with corporate actual cash taxes paid. In particular, revenues, intangible assets, and percentage of foreign shareholdings are found to increase corporate actual cash taxes paid, thereby leading to conservative tax planning schemes that reduce tax avoidance. The result also suggests that Big-4 accountancy firms, tax haven status and firm size are negatively and significantly associated with corporate actual cash taxes paid. Consequently, it is recommended that the Federal Inland Revenue Service should monitor the revenue and intangible assets of companies through their annual fillings. Another recommendation is that relevant government agencies should encourage foreign equity participation in Nigerian companies. Finally, they should collaborate to provide policy changes that would increase the participation of Non-Big-4 accounting firms in auditing companies’ financial statements in Nigeria.